2015
DOI: 10.1002/jemt.22489
|View full text |Cite
|
Sign up to set email alerts
|

Mouse brain magnetic resonance microscopy: Applications in Alzheimer disease

Abstract: Over the past two decades, various Alzheimer's disease (AD) trangenetic mice models harboring genes with mutation known to cause familial AD have been created. Today, high-resolution magnetic resonance microscopy (MRM) technology is being widely used in the study of AD mouse models. It has greatly facilitated and advanced our knowledge of AD. In this review, most of the attention is paid to fundamental of MRM, the construction of standard mouse MRM brain template and atlas, the detection of amyloid plaques, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…A recent study of five diffeomorphic image registration algorithms have shown that Geodesic-SyN [11] is remarkable successful for mouse brain registration. Here, we used the optimal parameters proposed by Fu [12] (gradient step length at 1, time points at 2, integration time discretisation step at 0.05, the Gauss parameters for the velocity field and deformation field at [3,2], CC as the similarity metric for diffeomorphic transform, whereas MI as the similarity metric for affine registration, the number of iterations is [100, 100, 30] , and window radius at 2). …”
Section: Determination Of Settings For Intersubject Mouse Brain Regismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of five diffeomorphic image registration algorithms have shown that Geodesic-SyN [11] is remarkable successful for mouse brain registration. Here, we used the optimal parameters proposed by Fu [12] (gradient step length at 1, time points at 2, integration time discretisation step at 0.05, the Gauss parameters for the velocity field and deformation field at [3,2], CC as the similarity metric for diffeomorphic transform, whereas MI as the similarity metric for affine registration, the number of iterations is [100, 100, 30] , and window radius at 2). …”
Section: Determination Of Settings For Intersubject Mouse Brain Regismentioning
confidence: 99%
“…Thus, atlas based brain segmentation has also been extended from human to mouse [2]. A number of groups have delineated brain ROIs in mouse MR microscopy (MRM) for atlas based parcellation .…”
Section: Introductionmentioning
confidence: 99%
“…The signal to noise ratio (SNR) is poor, morphological change is more subtle, and brain anatomy is quite different [15], which raise the question to existing registration algorithms. The performance of SyN registration is subject to several adjustable parameters(regularization, similarity measures in transformation, transformation model, iterations and window radius).…”
Section: Optimizing Strategymentioning
confidence: 99%
“…Transgenic mice (Van der Weyden & Bradley, ) have been widely used in neuroscience research for understanding the mechanism of disease‐related abnormalities such as AD (Alzheimer's Disease), PD (Parkinson's Disease) etc. (Schaeffer et al ., ; Lin et al ., ; Perruolo et al ., ). Ultra‐high magnetic field, matched physical devices and optimised acquisition sequences are required to develop MRI at microscopy level as magnetic resonance microscopy (MRM) (Driehuys et al ., ; Badea & Johnson, ).…”
Section: Introductionmentioning
confidence: 97%
“…Transgenic mice (Van der Weyden & Bradley, 2006) have been widely used in neuroscience research for understanding the mechanism of disease-related abnormalities such as AD (Alzheimer's Disease), PD (Parkinson's Disease) etc. (Schaeffer et al, 2011;Lin et al, 2015;Perruolo et al, 2016). Ultra-high Correspondence to: Lan Lin, Biomedical Engineering Department, College of Life Science and Bioengineering, Beijing University of Technology, Beijing 100124, China.…”
Section: Introductionmentioning
confidence: 99%